8+7m=m-4

Simple and best practice solution for 8+7m=m-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8+7m=m-4 equation:


Simplifying
8 + 7m = m + -4

Reorder the terms:
8 + 7m = -4 + m

Solving
8 + 7m = -4 + m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
8 + 7m + -1m = -4 + m + -1m

Combine like terms: 7m + -1m = 6m
8 + 6m = -4 + m + -1m

Combine like terms: m + -1m = 0
8 + 6m = -4 + 0
8 + 6m = -4

Add '-8' to each side of the equation.
8 + -8 + 6m = -4 + -8

Combine like terms: 8 + -8 = 0
0 + 6m = -4 + -8
6m = -4 + -8

Combine like terms: -4 + -8 = -12
6m = -12

Divide each side by '6'.
m = -2

Simplifying
m = -2

See similar equations:

| 10-(x-7)+2x=5 | | r^2-3=2r | | 2=-2b-8 | | -17+3(.25)=x | | 6n-3=4+5n | | 4g=5 | | X^2+5x-24=-6+2x | | 10+X=-30 | | (X+6)(X-8)(2x-7)=0 | | -8(t+9)=6 | | 3x-1+4x+3=180 | | 5b^2+31b+30=0 | | y^2-4x^2=16 | | 6=7s-4 | | 2+2p=2-2p | | 1.82=Log(x) | | 2(-4)-3=x | | 5x+4=6x-42+8 | | 7+m=6 | | 2p+4p-7x+3=4p+5-3x | | -5x-6=-1 | | V^2-2v-5=-3v-3 | | 12x-8=15x-14 | | -5(x-3)=5(x-3) | | 5m+3n-2m-8n= | | (x+2)(7x+8)=0 | | 9-4+5h+3x= | | 9x/2=3x | | 9-4+53+32= | | 25c^2-121g^2=0 | | Y=3/4x-9;(-8,-18) | | 4y+10=-26 |

Equations solver categories